2012
DOI: 10.1016/j.nano.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive silica-based nanoparticles stimulate bone-forming osteoblasts, suppress bone-resorbing osteoclasts, and enhance bone mineral density in vivo

Abstract: Bone is a dynamic tissue that undergoes renewal throughout life by a process whereby osteoclasts resorb worn bone and osteoblasts synthesize new bone. Imbalances in bone turnover lead to bone loss and development of osteoporosis and ultimately fracture, a debilitating condition with high morbidity and mortality. Silica is a ubiquitous biocontaminant that is considered to have high biocompatibility. We report that silica nanoparticles mediate potent inhibitory effects on osteoclasts and stimulatory effects on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
204
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(213 citation statements)
references
References 44 publications
6
204
0
3
Order By: Relevance
“…Interactions of NPs with cellular proteins can also lead to abnormal cytophysiology of the cell [46]. Except nanoparticle-mediated changes in protein folding, NPs can trigger different effects on physiological proteins involved in signal transduction and posttranslational modifications [27,47,48]. It was observed that super-paramagnetic iron oxide nanoparticles could affect signaling transduction pathways, through an increase in expression of genes responsible for production of tyrosine kinases and several members of the kinase C family [49].…”
Section: Interactions Between Nanoparticles and Organic Macromoleculesmentioning
confidence: 99%
“…Interactions of NPs with cellular proteins can also lead to abnormal cytophysiology of the cell [46]. Except nanoparticle-mediated changes in protein folding, NPs can trigger different effects on physiological proteins involved in signal transduction and posttranslational modifications [27,47,48]. It was observed that super-paramagnetic iron oxide nanoparticles could affect signaling transduction pathways, through an increase in expression of genes responsible for production of tyrosine kinases and several members of the kinase C family [49].…”
Section: Interactions Between Nanoparticles and Organic Macromoleculesmentioning
confidence: 99%
“…To overcome this, possible strategies are to optimize the topography or to mix it with another material that can activate cell growth [4]. Silicon oxide supports cell growth and hence can be used as the other phase in the mixture [5]. Another advantage of adding silicon oxide would be the improvement in mechanical stability and abrasive-wear resistance of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were cultured in α-Modified Eagle's Medium (Thermo Fisher Scientific, Waltham, MA, USA) supplemented with 10% fetal bovine serum (FBS; Atlanta Biologicals, Lawrenceville, GA, USA) supplemented with 1% lglutamine (Thermo Fisher Scientific) and 1% of penicillin/ streptomycin (Thermo Fisher Scientific). 15 All cell lines were cultured at 37°C in 5% CO 2 . Cell viability was measured using a commercial 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxyl-methoxyphenyl)-2-(4-sulfonyl)-2H-tetrazolium (XTT) assay according to the manufacturer's protocol (Promega Corporation, Fitchburg, WI, USA) as described previously.…”
Section: Cell Culture Studiesmentioning
confidence: 99%